Self-management Support of Diabetes Type 2 Patients in Bulgaria: Analysis of Biographical Intervi - Balkanska, Velina (Research Papers, 2016)
The article presents the main topics related to the lifestyle of patients diagnosed with type 2 diabetes based on an analysis of biographical interviews. The paper examines the content of the concept of self-management and provides an analysis of research on the impact of social networks – their mechanisms and practices. A scheme of thematic analysis of the biographical narratives is developed and key categories, topics and subtopics with relevant quotes are offered to illustrate patients’ self-management process. The levels of analysis include individual-perceptual level; social-categorical level associated with social network analysis and macroorganizational level, dealing with system factors. Conclusions are made both for the serious methodological potentials of biographical interviewing in health sociology and the overall description of the process of self-management of patients with type 2 diabetes in Bulgaria.
Keywords: Health; Diabetes type 2 patients; Self-management support; Biographical interviews; Social media